2016
DOI: 10.1177/0272989x16660547
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians’ Support of Shared Decision Making for Different Cancer Screening Decisions

Abstract: Background Despite widespread advocacy, shared decision making (SDM) is not routinely used for cancer screening. To better understand implementation barriers, we describe primary care physicians’ (PCPs’) support for SDM across diverse cancer screening contexts. Methods Mailed survey administered to random sample of US-based PCPs. Using multivariable logistic regression we tested association of PCPs’ SDM support with US Preventive Service Task Force (USPSTF) assigned recommendation grade, whether decision per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…By fulfilling the role of decision coaches (Stacey et al, 2012; Stacey et al, 2008), nurses prepare individuals to have conversations with their practitioners about screening decisions (Grad et al, 2017; Lang et al, 2018; RNAO, 2015; Stacey et al, 2008). However, providers also face organizational barriers such as performance quality metrics that might impede shared decision-making (Elston Lafata et al, 2017; Walter & Lewis, 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By fulfilling the role of decision coaches (Stacey et al, 2012; Stacey et al, 2008), nurses prepare individuals to have conversations with their practitioners about screening decisions (Grad et al, 2017; Lang et al, 2018; RNAO, 2015; Stacey et al, 2008). However, providers also face organizational barriers such as performance quality metrics that might impede shared decision-making (Elston Lafata et al, 2017; Walter & Lewis, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Shared decision making provides an opportunity to implement evidence-based practice that accounts for patient preferences, such that when multiple options are available to patients regarding a specific health decision, individuals’ personal characteristics and values will influence the best choice for them (Hoffmann et al, 2014; Stacey et al, 2017). However, the use of shared decision making in cancer screening is seldom used and such approaches that have been used are diverse (Elston Lafata, Brown, Pignone, Ratliff, & Shay, 2017; Hoffmann et al, 2014). …”
mentioning
confidence: 99%
“…By providing recent evidence on the cervical screening modalities that are available, women who use this tool can compare the current options independently, prior to a clinical encounter. With a balanced, nondirective design, women might feel more confident to ask for their preferred option in an encounter with a provider, particularly if their preference diverges from the provider's preference …”
Section: Discussionmentioning
confidence: 99%
“…With a balanced, nondirective design, women might feel more confident to ask for their preferred option in an encounter with a provider, particularly if their preference diverges from the provider's preference. [52][53][54] Beyond the individual level, we used a shared decision-making framework to develop an approach that can be used to elicit preferences among a population-based sample. Some experts are wary of applying population preferences in individual encounters for cancer screening because extrapolating might be inaccurate or ignore individual's autonomy in decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of shared decision‐making in breast, colorectal and prostate cancer screening revealed that patient/provider communications are often ineffective . Elston Lafata et al .…”
Section: Introductionmentioning
confidence: 99%